PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI LEMBAGA PENYIARAN PUBLIK RRI KENDARI - Wisnu Maulana Saputra; Samdin Samdin; Agustinus Tangalayuk; Yusuf Montundu; Ansir Ansir; Hartini Hartini (Jurusan Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Halu Oleo, 2023)
This study aims to examine and analyze the effect of compensation and work discipline on employee performance. This study uses a sampling technique, namely a saturated sample of 61 samples consisting of a secretary, head of division, head of section, and functional staff of the RRI Kendari Public Broadcasting Institute. Methods of data collection using a questionnaire. The data analysis method uses multiple linear regression analysis with the help of the IBM SPSS Statistics Version 24 software application.The results of this study indicate that (1) Compensation partially has a positive effect on employee performance. (2) Work Discipline partially has a positive effect on employee performance. (3) Compensation and Work Discipline simultaneously have a positive effect on employee performance. The conclusion of this study is that the higher the compensation, the higher the performance of the resulting employee as well as the higher the work discipline, the higher the employee's performance, and compensation and work discipline have an interaction with the employee's performance.